Frequency of Immunohistochemical Marker GPC-3 Expression in Malignant Tumors - Noshaba Rahat, Humera Shahzad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of immunohistochemical marker GPC-3 expression in malignant tumours in a tertiary care hospital. Material & Methods: This cross sectional study was conducted at the department of Histopathology, Dr. Ziauddin Medical University and Hospital, north campus, Karachi, a total of 114 cases of malignant tumours were enrolled using consecutive sampling technique in a period of six months from 1st April, 2012 to 30th September, 2012. Patients of both genders and all age groups of histologically diagnosed case of hepatocellular carcinoma (HCC) metastatic tumours, germ cell tumours (GCT) and squamous Cell Carcinoma (SCC) were all included in the study. The patients with benign tumours, malignant lymphoma, brain tumours, breast tumours, colon carcinoma and malignant melanoma were excluded from the study. The study outcome was determined as frequency of positive GPC-3 expression. Results: A total of 114 cases were enrolled. Average age was 48.8 years with majority of cases (70.4%) were 40 years or above age. Male gender was slight dominance (53.5%). Squamous cell carcinoma was the most common (78.9%) followed by, germ cell tumours (10.5%) including (6.1%) yolk sac tumour and 4.3% Germinoma. Hepatocellular carcinoma was found in (6.1%) study cases. Most of the cases (45.6%) were moderately differentiated (SCC and HCC),followed by poorly (42.1%) and well differentiated (12.3%) grading. The frequency of positive GPC-3 expression was 25.4% in all malignant tumour in the current study. It is diagnostic and accuracy is more than other markers for definitive diagnosis and tp differenciate between primary and metastatic tumors. Conclusion: In conclusion out of 114 cases 25.4% of total cases show GCP-3 positively, among which GCT were 24.1% and HCC were 85.7% which is quite similar to other reported studies. Type of the tumour was found to be significantly associated with the age group above 40 years (P=0.000). There is significant association between type of tumour and GCP-3 expression (P=0.000). Keywords: Malignant Tumours, SCC, HCC GCT, GPC, GPC-3 expression